1938
DOI: 10.1152/ajplegacy.1938.124.3.800
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hydrogenation and Oxidation of Fats Upon Their Rate of Absorption

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1949
1949
1962
1962

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Lassen et al (1949) found that heat polymerization of a number of oils, including herring oil, resulted in some factor(s) which depressed rat growth and efficiency of feed utilization. Irwin et al (1938) found that the rate of absorption of hydrogenated fat by the rat varied inversely with the degree of oxidization. Witting et al (1957) com-pared the effects of thermally polymerized and autoxidized fish oil when fed to rats at a level of 10% of the diet and concluded that thermally polymerized fish oil was more harmful than was oxidatively polymerized oil.…”
mentioning
confidence: 98%
“…Lassen et al (1949) found that heat polymerization of a number of oils, including herring oil, resulted in some factor(s) which depressed rat growth and efficiency of feed utilization. Irwin et al (1938) found that the rate of absorption of hydrogenated fat by the rat varied inversely with the degree of oxidization. Witting et al (1957) com-pared the effects of thermally polymerized and autoxidized fish oil when fed to rats at a level of 10% of the diet and concluded that thermally polymerized fish oil was more harmful than was oxidatively polymerized oil.…”
mentioning
confidence: 98%